THE REPRESENTATION OF SEXISM IN POOR THINGS MOVIE (2023) - Ritanty Syarifudin; Esterria Romauli Panjaitan; Winda Lutfiyanti (Universitas Wiralodra, 2025)
The study examines how sexism is depicted through the experiences of the main character, Bella Baxter, as shaped by other characters. It adopts a qualitative descriptive method by examining dialogues, characters, and narrative aspects that reflect sexism through textual analysis. Cudd and Jones's (2003) levels of sexism theory and Glick and Fiske's (2018) ambivalent sexism theory are applied to examine the movie's portrayal of sexism. These theories complement each other, with Cudd and Jones (2003) focusing on the societal and institutional components of sexism, while Glick and Fiske (2018) emphasize how sexism appears in both benevolent and hostile ways within interpersonal interactions. The findings show that Bella confronts both hostile and benevolent sexism, such as paternalistic control, objectification, and intimidation. Furthermore, the movie depicts various levels of sexism, as Bella faces interpersonal, institutional, and unconscious sexism. These sexist interactions initially restrict her autonomy, reinforcing gender-based power imbalances. However, Bella escapes these limitations, restoring her agency. The movie critically investigates the widespread impact of sexism and how it influences women's social positioning and self-perception. Future researchers are expected to explore this topic on a wider scope